Artesunate improves cryopreserved yak sperm quality by activating SOD1 antioxidant pathway - Fan, Yilin; Lv, Weibing; Li, Xiaowei; Wanma, Geri; Li, Jian; Xiong, Xianrong; He, Xiaoqiang; Wang, Yanwen; Yin, Shi; Fu, Wei; He, Honghong; Lin, Yaqiu; et al. (Frontiers in Veterinary Science, 2025)
IntroductionSperm damage from oxidative stress is common in semen cryopreservation. Natural antioxidants for frozen semen are largely unexplored. Artesunate (ART), derived from Artemisia annua and used for malaria treatment, shows potential as a frozen semen antioxidant.MethodsWe investigated the effects of various ART concentrations (0.2, 0.5, and 1.0 mM) on yak semen cryopreservation and examined the molecular mechanisms involved.ResultsPost-freezing, sperm quality markedly declined. However, 0.2 mM ART significantly improved sperm motility (both total and progressive) and reduced membrane damage. ART treatment effectively alleviated oxidative stress by reducing ROS levels and MDA content in the sperm while selectively upregulating SOD1 activity and protein levels, which are involved in maintaining DNA integrity and mitochondrial function.ConclusionThese findings support the hypothesis that ART exerts antioxidant effects via a SOD1-mediated mechanism, highlighting its potential to improve frozen semen quality and offering a novel strategy for cryopreserving sperm in other species.